Nanoneuroscience and Nanoneuropharmacology - Sharma, H. S. (Hari Shanker) (Progress in brain research, 2009)
This volume presents articles from the leading experts in the field in nanobiotechnology providing students and researcher a comprehensive review of the newly emerging area of neuroscience. All aspects of nanomaterials induced alteration in brain function are considered. Basic chapters on methods and ways to enhance nano-drug delivery into the brain are presented as well as chapters on functional and structural changes in the CNS, including gene expression and related issues. Particular attention is given to possible therapeutic advancement regarding nano-drug formulation and their role in neuroprotection.